Accelerating Progress toward Millennium Development Goals (MDGs) 2010 – 2015: Can Tanzania Inform the Future? - Karamagi, Innocent (Tanzania Journal for Population studies and Development, 2012)
This paper examines the progress that Tanzania has made toward achieving the Millennium Development Goals (MDGs), and takes a glimpse at issues that will be pertinent for Tanzania in the post-2015 agenda, when the MDGs expire. Whereas goals with regard to primary school enrolment, gender equality, child mortality and containing HIV and AIDS and malaria are indicating to be achievable, goals with regard to poverty, hunger and maternal mortality will not be achieved. It is noteworthy that the progress toward MDGs has been marked by a number of conundrums; persistent inequalities, especially between urban and rural areas; poor outcomes in terms of quality despite meeting output targets; limited links between goals that do not reflect the effects of synergies; and lack of incorporation of vulnerability issues. All these issues as well as MDGs that are yet to be achieved should be at the core of the new development agenda for the post-2015 period.